Oral submucous fibrosis: a study of qualitative and analytical treatment using intralesional injections: placental extract versus combination of steroid with hyaluronidase - Kale, Meena Vishwanath; Gaikwad, Ninad Subhash (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: One of the premalignant conditions in oropharynx is oral submucous fibrosis (OSMF). It is a chronic debilitating condition of unknown etiology leading to fibrosis of mucosa affecting the oropharynx, esophagus and thus causes decreased mouth opening and dysphagia respectively. The disease is of multifactorial etiology with addictions, nutritional, micro elements and antioxidants deficiencies. In India males are more affected than females, due to their stress related excessive, irresponsible chewing habits. The available management is for symptomatic relief and at present there is no definitive treatment is available. Methods: We have studied 60 cases diagnosed with OSMF with mild to moderate restricted mouth opening. Most of patients were between 17 to 55 years of age selected by randomized clinical trial. Its management was divided into 2 groups where group A was treated with a combined intralesional regimen of injection triamcinolone 40mg and hyaluronidase 1500 IU, while group B was treated with injection of 2ml placental extract. Each group has given a single dose intralesional injection per week for six weeks. Results: It was a comparative study of improvement in effectiveness on mouth opening and reduction in burning sensation of oral cavity seen in group A regimen than group B. Those having persistent trismus, needed surgery. Conclusions: No effective treatment available but along with intralesional injection can give symptomatic relief. In addition, cessation of habits, antioxidants oral hygiene helps in improvement of OSMF.